(untitled) (Journal of Science and Technology, 2016)
Samples of Dusa, a cereal by-product derived from \’koko\’ (porridge) production, from twenty \’koko\’ producers located at Aboabo, Akwatia Line, Dagomba Line, Adukrom, Roman Hill and Sabon-Zongo, all suburbs of Kumasi in the Ashanti Region of Ghana were analysed to determine nutrient composition, establish the extent of availability, the current and potential uses. Questionnaires were administered at each production site to determine, inter alia, the type of cereals used, production processes, the extraction rate and cost (¢/kg) of dry Dusa. The samples were analysed for their proximate composition and (%) NDF, ADF and Hemicellulose. The mean DM, CP, EE, CF, Ash and NFE ranged between 89.58-93.02, 10.51-21.86, 1.42-5.38, 4.70-10.77, 0.68-4.55 and 58.29-68.89% respectively and the corresponding mean NDF, ADF and Hemicellulose ranged from 27.56-62.47, 6.52-14.95 and 18.76-50.08%. There were significant (p < 0.05) differences between the products from the different sites with respect to their DM, CP, CF, Ash and NFE contents. The survey showed that mainly backyard farmers patronised Dusa and the data collected indicated that the extraction rate for Dusa was 9.02%. The price of dry Dusa ranged between ¢200.00 and ¢300.00/kg. Dusa is comparable to other cereal by-products such as rice bran, maize bran, wheat bran, etc. in nutrient composition and can therefore be used in ration formulation for both ruminant and non-ruminant livestock